DEVELOPMENT OF THERMAL INSULATION BY UTILIZNG EMPTY FRUIT BUNCH (EFB) - Azizuddin, Aliah Azlin (IRC, 2016)
Thermal insulation has been developed to prevent the heat loss in order to maintain the current temperature and pressure. The purpose of insulation is to reduce the heat losses and increase the efficiency. The experiment was conducted to study a potential of utilizing empty fruit bunch (EFB) as a thermal insulation. A two-stage methodology was used in this study, which are the characterization of the empty fruit bunch and thermal conductivity test by using P.A Hilton, Thermal Conductivity Measuring Unit (B480). The results of the thermal conductivity were compared with selected insulation material which is rock wool and Oil Palm Fiber. In the characterization stage, the specimen went through Proximate and Ultimate Analysis. The objectives of the characterization is for comparison purposes. The container for densities was prepared by using 30cm x 30cm x 4.5cm.